Analisis Komparatif Implementasi Robot Line Follower: Studi Literatur Perbandingan Sistem Berbasis Mikrokontroler Arduino dan Sistem Analog Tanpa Mikrokontrole - Afifuddin, Afifuddin; Sukamdani, Sukamdani; Syafaat, Mokhammad (Jurnal Elkasista, 2024)
This study presents a comparative analysis of line follower robot implementation by examining two primary system approaches: Arduino microcontroller-based systems and analog systems without microcontrollers. Employing a qualitative descriptive method through literature review, this research synthesizes scholarly publications from reputable databases spanning 2018 to 2025. The analysis emphasizes key technical aspects, including sensor configurations, control algorithms (notably PID), power efficiency, as well as each system’s operational stability and adaptability. The findings reveal that Arduino-based systems excel in programming flexibility, multi-sensor integration, and ease of algorithmic modification. Nevertheless, these systems face challenges regarding power consumption and processing latency. Conversely, analog systems offer rapid response and high energy efficiency but lack flexibility in adapting to changing operational environments. This study establishes a conceptual framework for selecting line follower robot systems tailored to specific application requirements, whether for industrial, educational, or research purposes. The implications serve as strategic insights for the development of precise, efficient, and contextually appropriate robotic systems.